2019
DOI: 10.1111/eci.13161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concomitant antiplatelet therapy in patients with nonvalvular atrial fibrillation initiating non‐vitamin K antagonists

Abstract: Background Antiplatelet therapy (APT) use in combination with oral anticoagulation is common among patients with atrial fibrillation, but there is scarce information regarding its effect on outcomes in patients on non‐vitamin K antagonist oral anticoagulants (NOAC). We aimed to evaluate the safety and efficacy of APT use in a ‘real‐world’ cohort of nonvalvular atrial fibrillation (NVAF) patients initiating NOAC. Design We conducted a retrospective multicentre study including 2361 consecutive NVAF patients init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“… [6] In the study by Ruiz et al, concomitant ASA was associated with higher rates of bleeding with no benefits in terms of ischemic protection. [12] The findings of Davidson et al study aligns with the findings of the previous studies that demonstrate that concomitant use of ASA is associated with an increased risk of major bleeding. [13] Tinkham et al study showed non-significant results for major bleeding between DOAC + APT and DOAC monotherapy.…”
Section: Discussionsupporting
confidence: 85%
“… [6] In the study by Ruiz et al, concomitant ASA was associated with higher rates of bleeding with no benefits in terms of ischemic protection. [12] The findings of Davidson et al study aligns with the findings of the previous studies that demonstrate that concomitant use of ASA is associated with an increased risk of major bleeding. [13] Tinkham et al study showed non-significant results for major bleeding between DOAC + APT and DOAC monotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…As anticoagulant and antiplatelet drugs inhibit different phases of hemostasis, their association can theoretically result in an increased hemorrhagic tendency. Clinically, a retrospective analysis found that antiplatelet use was rare in non‐HD patients treated with DOACs for atrial fibrillation (145/2361 [6.1%]) and that concomitant use of antiplatelets and DOACs increased bleeding risk approximately 3.5‐fold at 3 months of follow‐up compared to apixaban alone 32 . Another large retrospective study of non‐HD patients reported a lower risk of major bleeding with concomitant DOAC‐antiplatelet use compared to warfarin‐antiplatelet (HR 0.68 [95% CI 0.51‐0.91]) 33 .…”
Section: Discussionmentioning
confidence: 99%